Correction: Reversible fluorescence modulation through the photoisomerization of an azobenzene-bridged perylene bisimide cyclophane. Issue 7 (16th March 2021) - Ouyang, Guanghui; Bialas, David; Würthner, Frank
Abstract : Correction for 'Reversible fluorescence modulation through the photoisomerization of an azobenzene-bridged perylene bisimide cyclophane' by Guanghui Ouyang et al., Org. Chem. Front., 2021, DOI: ; 10.1039/D0QO01635G .